Upaya Hukum Lembaga Pembiayaan Dalam Hal Terjadinya Pengalihan Objek Perjanjian Dalam Perjanjian Sewa Beli Kendaraan - Rio Febrianto; Diah Apriana; Fauzan Pramana; Ria Wantika Sari; Daniel Christianto; Marsudi Utoyo (Consensus : Jurnal Ilmu Hukum, 2022)
Currently, the lease purchase agreement in Indonesia is growing rapidly. This can be seen in everyday life because there are many people who support the agreement, especially to meet its secondary needs. In a rental agreement to buy a vehicle, as one of the types of an unnamed agreement, the legal effort of the funding agency in respect of the transfer of the object of the agreement. It is a normative jurisprudence that only looks at library material or secondary data that can include primary, secondary, or tertiary legal material. The legal effort that a creditor may make, as regulated in article 1243 of the Code of Civil Procedure, relates to the creditor's right to claim damages for the default of the debtor. In addition, in accordance with the provisions listed in the agreement of Article 6a paragraph (4) mentioned above, and in conformity with Article 1266 of the Code of Procedure, the creditor may also cancel the agreements. The creditor may also steal the vehicle which is the object of the agreement; in this case, the debtor must surrender the vehicle. In accordance with Section 30 of the Trust Guarantee Act No. 42 of 1999.